Rendimiento de 16 híbridos de sorgo granifero bajo infestación natural de Malanaphis sorghi (Theobald, 1904) (Hemiptera: Aphididae) - Guillot Giraudo, Walter; Babinec, Francisco Jose; Dillchneider Loza, Alexandra; Figueruelo, Andrea Mariana; Funaro, Daniel Oscar (Universidad Nacional del Noroeste de la Provincia de Buenos Aires (UNNOBA); INTA, 2024)
Poster